Addressing the Decline in Clinical Skills: A Call for Comprehensive Educational Reform - Muhammad Noor Wazir (Gandhara University, 2024)
Despite technological advances, clinical skills are the foundation of medical practice. Taking a comprehensive clinical history, performing physical examinations, and communicating effectively are crucial for high-quality patient care. Medical students need to focus on developing strong clinical skills to ensure they are well-prepared for their careers and adapt to the evolving field of medicine through continual practice and refinement.1 The medical community is worried about declining essential clinical skills among undergraduate medical students.2,3 This editorial aims to analyze the reasons for the decline and suggest evidence-based methods to address the situation. 05885.0258063. The declining standards of clinical skills among medical students can be attributed to the widespread adoption of technology-based learning, which has the potential to diminish the importance of traditional hands-on bedside teaching.4 Technology should enhance, not replace, practical clinical experiences. Practical training improves the clinical abilities, expertise, and self-assurance of medical students.5 Moreover, the growing magnitude and expansion of medical curricula provide difficulties in the development of educational programs without ample time for bedside practical teaching.6,7 There is frequently an excessive focus on remembering facts rather than on cultivating clinical reasoning abilities.8 The reduced patient interaction during medical school, due to increased reliance on simulations and less time in clinical rotations and bedside teaching, hampers the development of clinical skills.9 External factors such as limited time and extensive paperwork may affect the quality of patient encounters. Efficient communication is crucial for building good relationships with patients, obtaining accurate medical histories, and ensuring patient understanding and adherence to treatment.9 Insufficient training in communication skills can result in less-than-ideal interactions between patients and healthcare providers and can also contribute to errors in diagnosis and medical treatment.10   The provision of trained faculty for teaching medical students is an issue worldwide. Insufficient supervision and feedback during clinical rotations hinder the development of essential clinical skills.11 Larger student cohorts reduce the opportunities for individual students to practice and receive personalized instruction in clinical skills.12 Medical education often prioritizes theoretical testing over practical examinations and undervalues communication skills training. Variability in clinical experiences at different medical schools can lead to inconsistencies in skill acquisition. The scarcity of skilled clinicians as role models impacts students' learning. Economic constraints and modern healthcare pressures limit opportunities for thorough patient interactions and clinical training.13   THE WAY FORWARD   Educational institutions should prioritize hands-on clinical experiences throughout the curriculum to improve students' diagnostic and communication abilities. These experiences should include simulation-based learning, standardized patients, and longitudinal clerkships. Faculty members need support and resources for effective clinical mentorship and development. Reflective practice should be integrated into the curriculum to enhance self-awareness and critical thinking. Open communication and mentorship programs between students and faculty can strengthen medical training and promote continual learning.   To address declining clinical proficiency among medical students, institutions can adopt evidence-based approaches including curriculum changes, faculty training, promoting reflective thinking, collaboration among healthcare professionals, and fostering a culture of ongoing learning. Regulatory bodies should ensure adequate time for bedside teaching and appropriate assessment weightage.